Epidermolysis Bullosa Acquisita: The 2019 Update - Koga, Hiroshi; Prost-Squarcioni, Catherine; Iwata, Hiroaki; Jonkman, Marcel F.; Ludwig, Ralf J.; Bieber, Katja (Frontiers in Medicine, 2019)
Epidermolysis bullosa acquisita (EBA) is an orphan autoimmune disease. EBA patients suffer from chronic inflammation as well as blistering and scarring of the skin and mucous membranes. Current treatment options rely on nonspecific immunosuppression, which in many cases, does not lead to a remission of treatment. Hence, novel treatment options are urgently needed for the care of EBA patients. During the past decade, decisive clinical observations and frequent use of pre-clinical model systems have tremendously increased our understanding of EBA pathogenesis. Herein, we review all of the aspects of EBA, starting with a detailed description of epidemiology, clinical presentation, diagnosis and current treatment options. Of note, pattern analysis via direct immunofluorescence microscopy of a perilesional skin lesion and novel serological test systems have significantly facilitated diagnosis of the disease. Next, a state-of the art review of the current understanding of EBA pathogenesis, emerging treatments and future perspectives is provided. Based on pre-clinical model systems, cytokines and kinases are among the most promising therapeutic targets, whereas high doses of IgG (IVIG) and the anti-CD20 antibody rituximab are among the most promising “established” EBA therapeutics. We also aim to raise awareness of EBA, as well as initiate basic and clinical research in this field, to further improve the already improved but still unsatisfactory conditions for those diagnosed with this condition.